PHYTOCHEMICAL ANALYSIS OF Enteromorpha flexuosa AND Ulva lactuca: A COMPARATIVE STUDY - S.SHARMILA; L.JEYANTHI REBECCA (International Journal of Pharma and Bio Sciences, 2014)
South coastal line of Tamil Nadu consists of a wide variety of seaweeds that are having abundant bioactive compounds which are useful in drug design. In this investigation, various solvent extracts of Enteromorpha flexuosa and Ulva lactuca were analyzed qualitatively of their bioactive compounds. Results revealed that extracts of U.lactuca have more phytochemical constituents than the extracts of E.flexuosa. Phenol, Tannin and cardiac glycosides were present in a higher amount in the extracts of E.flexuosa. Cardiac glycoside and phlobatanin was found to be abundant in the extracts of U.lactuca. Amino acids and carbonyl compound were found to be absent in both algal extracts.